Study on aerodynamic drag and noise reduction of high-speed pantograph with streamwise holes - Tian Li; Deng Qin; Xiang Kan; Jiye Zhang (Engineering Applications of Computational Fluid Mechanics)
Exploring ways to minimize drag and noise for high speed train pantographs is critical. This study investigates the effects of incorporating holes in the panhead as a potential solution for reducing drag and noise. Using an improved delayed detached eddy simulation (IDDES) model and applying the Ffowcs Williams and Hawkings (FW-H) equation for far-field noise prediction, the aerodynamic characteristics of pantographs with and without holes are analyzed and compared. The results show that opening a streamwise hole on the panhead of the pantograph can affect the vortex in the wake when the airflow flows through the pantograph, thereby changing the pressure distribution in the wake and reducing the fluctuating pressure on the surface of the pantograph. The analysis of the aerodynamic force, fluctuating pressure, turbulent kinetic energy and vortex structure of the panhead with or without streamwise holes shows that the panhead with holes has lower aerodynamic drag and noise level. Adding streamwise holes to the panhead results in a 20.81% reduction in aerodynamic drag and lowers the far-field noise level by 1.41 dBA. The research results can provide data support and reference for the development of higher speed pantograph.